Analisis Risiko Hukum dalam Kontrak Bisnis Internasional Oleh Korporasi - Ismaidar Ismaidar; Kevin Maisyan Rizaldi Mendrofa; Angga Sahputra Sirait (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
International business contracts are the main tool in global trade activities. However, the complexity of laws between countries gives rise to various legal risks that can be detrimental to corporations. In practice, differences in national legal systems, inappropriate choice of law, jurisdictional uncertainty, and differences in interpretation of contract clauses are often the main causes of disputes. Legal risks can also arise due to non-compliance with local laws, changes in government policies, and force majeure conditions that are not adequately anticipated in contracts. This study aims to analyze the types of legal risks in international business contracts and mitigation strategies that can be applied by corporations. This study uses a normative legal approach method with data collection techniques through literature studies of international regulations, doctrines, and practices. The results of the study indicate that differences in legal systems, jurisdictional uncertainty, and force majeure and arbitration clauses are crucial issues that must be anticipated strategically. The application of the principle of prudence in drafting contracts and the selection of appropriate laws and dispute resolution forums are the keys to the success of legal risk mitigation.